main algebraic solution

Mathematics
Tutor: None Selected Time limit: 1 Day

May 28th, 2015

You use the same principle

f'(x)=2ax+b

f'(-1)=0 <=>-2a+b=0 <=>b=2a

f(x)=ax^2+2ax+c

f(-1)=-4 and f(-4)=-8

a-2a+c=-4 and 16a-8a+c=-8

-a+c=-4 and 8a+c=-8

9a=-4 and -a+c=-4 

a=-4/9 and c=-40/9

f(x)=-4/9x^2-8/9x-40/9

May 28th, 2015

Are you studying on the go? Check out our FREE app and post questions on the fly!
Download on the
App Store
...
May 28th, 2015
...
May 28th, 2015
Dec 4th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer